FishIdentification in the Sei Paku Reservoir, Kampar Kiri Sub-District, Kampar Districts, Riau Province - Melinda, Devi; Efizon, Deni; Putra, Ridwan Manda (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThe Sei Paku Reservoir is inhabited by many fish species, but they never been studied.A study aims to understand the type of fish present in the reservoir, has been conducted in February to April 2019. Fish sampling were conducted six times once/two weeks. The fishes were captured using lures, gill nets and bamboo traps. Fish samples were then identified.Results shown that there were 21 fish spesies and they were belonged to 10 families, 15 genus, and 4 ordo. Among 21 species captured, 2 species were categorized as ornamental fish, 9 species were consumtion fishand 10 species were ornamental-consumtion fish.The water quality of the reservoir were as follows: temperature of 28°C-32°C, brightness of 26.15-58 cm, pH of 6, disolved oxygen of 3-5 mg/L and carbondioxide 5.99-7.99 mg/L. Keywords: Sei Paku Dam, Ornamental fish, consumtion fish, ornamental- consumtion fish